Portrait of Williams Haynes (1886-1960) (1950)
Portrait of Williams Haynes (1886-1960). Williams Haynes was born on July 29, 1886 in Detroit, Michigan. After graduating from high school, Haynes worked as a reporter for the New York Sun before enrolling at Johns Hopkins University in 1908, where he studied economics, biology, and chemistry. Haynes left Johns Hopkins in 1911 and went on to have a prolific career as an author and editor specializing in the chemical industry. In 1928, Haynes established the Chemical Who’s Who series and served as its editor until 1951. During this time, Haynes also published several monographs on various aspects of the history of the American chemical, including Chemical Economics (1933), Men, Money, and Molecules (1935), Chemical Pioneers (1939), and This Chemical Age (1942), as well as the multi-volume American Chemical Industry: A History (1945-1954).
Keywords: Journalists; Haynes, Williams, 1886-1960; Portraits